Implications of nanoparticles functionalization in supramolecular magnetogels for drug delivery - Veloso, Sérgio Rafael Silva (2021)
In this work, dehydropeptide gels were loaded with citrate- or lipid-stabilized nanoparticles to evaluate the effect over doxorubicin release. Particularly, the lipid-stabilized nanoparticles co-assembled with the hydrogel fibres forming lipid-fibre interface domains.